Potassium application to the cover crop prior to cotton planting as a fertilization strategy in sandy soils - Echer, Fabio Rafael; Souza Peres, Vinicius Jose; Rosolem, Ciro Antonio [UNESP] (Nature Research, 2020)
Urochloa grasses are used as cover crops in tropical cropping systems under no-till to improve nutrient cycling. We hypothesized that potassium (K) applied to ruzigrass (Urochloa ruziziensis) grown before cotton in a sandy soil could be timely cycled and ensure nutrition, yield and quality of cotton cultivars with no need to split K application. Field experiments were performed with different K managements, applied to ruzigrass, to cotton grown after grass and without grass, or split as it is done conventionally. No yield differences were observed on K fertilized treatments. At 0 K, cotton yields were low, but they increased by 16% when ruzigrass was grown before, and short fiber content was lower when there was more K available. Ruzigrass grown before cotton increased micronaire as much as the application of 116 kg ha(-1) of K without the grass. Fiber maturity was higher when K was applied to the grass or split in the grass and sidedressed in cotton. Growing ruzigrass before cotton allows for early K fertilization, i.e., application of all the fertilizer to de grass, since the nutrient is recycled, and cotton K nutrition is not harmed. Eventually K rates could be reduced as a result of higher efficiency of the systems.